1982
DOI: 10.1128/iai.36.1.271-276.1982
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Salmonella resistance and delayed hypersensitivity with murine-derived transfer factor

Abstract: Protective host immunity and delayed hypersensitivity were transferred to nonimmune ICR and C3H/HeJ mice with transfer factor prepared from the splenic lymphocytes of ICR Swiss mice immune to Salmonella typhimurium. Only mice injected with the "immune" dialysate exhibited significant footpad swelling (P less than 0.01) to a spent medium antigen of S. typhimurium, but not Listeria monocytogenes. Host survival to a lethal Salmonella challenge infection was seen only in transfer factor-injected mice. Also, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Morris et al (23) found that immunosuppression of B cells, but not T cells, in vaccinated mice permitted their avirulent vaccine strain to grow out in the host and to be lethal for the vaccinated animals. Smith et al (35) reported that spleen cells and splenic transfer factor prepared from mice given a live vaccine 2 weeks previously transferred delayed-type hypersensitivity to Salmonella and low levels of protection (25%) as measured at 30 days postchallenge, but did not specify the cell type responsible for the transfer of immunity. (We find that many hypersusceptible mice die between 30 and 60 days, so 30 days may not be a valid endpoint.)…”
mentioning
confidence: 99%
“…Morris et al (23) found that immunosuppression of B cells, but not T cells, in vaccinated mice permitted their avirulent vaccine strain to grow out in the host and to be lethal for the vaccinated animals. Smith et al (35) reported that spleen cells and splenic transfer factor prepared from mice given a live vaccine 2 weeks previously transferred delayed-type hypersensitivity to Salmonella and low levels of protection (25%) as measured at 30 days postchallenge, but did not specify the cell type responsible for the transfer of immunity. (We find that many hypersusceptible mice die between 30 and 60 days, so 30 days may not be a valid endpoint.)…”
mentioning
confidence: 99%
“…We have recently demonstrated that Salmonella typhimurium-immune ICR Swiss and C3H/HeJ mice exhibit more than 0.22% Salmonella antigen-specific rosette-forming lymphocytes (RFL), which correlated directly with the ability of the recipients to survive a challenge with virulent Salmonella (3). TF prepared from the spleens of S. typhimurium-immune ICR Swiss mice can confer host protection and positive footpad swelling responses to nonimmune ICR Swiss and C3H/HeJ mice (23).…”
mentioning
confidence: 98%